Alpine Landschaft per Bahn. Die Bergmenschen bei Peter Rosegger und Heimito von Doderer - Roland Tusch (Góry, Literatura, Kultura)
The construction of railways made the mountains accessible to urban society in the age of industrialisation. The construction of the world’s first high mountain railway, the Semmering Railway, was followed by the development of Alpine summer resorts for tourists, very close to Vienna. Texts of the two Austrian writers Peter Rosegger (1843–1918) and Heimito von Doderer (1896–1966) offer the op- portunity to approach the people and their relationship to the mountains and the Semmering Railway. The analysis explores the questions: How did Rosegger experience the development of the mountains by the railway? How do Rosegger and Doderer’s travellers on the train experience the mountains? How do Rosegger and Doderer describe the people who came to Semmering because of the railway?